PENERAPAN PIDANA TERHADAP ANAK PELAKU TINDAK PIDANA PERSETUBUHAN (Studi Putusan Nomor 3/Pid.Sus-Anak/2018/PN.Pmn dan Putusan Nomor 11/Pid.Sus-Anak/2018/PN.Pmn) - Koesoemowardani, Rahmani Endah (UNES Law Review, 2019)
The verification of this crime is often not carried out properly, because the child of the victim of sexual intercourse feels embarrassed and afraid of the perpetrators, which influences the judgment of the judge and the application of the law. The criminal application of the Pariaman District Court Number 3 / Pid. . Pmn and Number 11 / Pid. Sus-Anak / 2018 / PN.Pmn is the criminal application of children as perpetrators of sexual intercourse in decision Number 3 / Pid.sus anak / 2018 / PN Pmn and Number 11 / Pid. Sus- Anak / 2018 / PN Pmn, Based on the legal facts revealed in the trial fulfilled the elements contained in Article 81 paragraph (2) of Law Number 35 Year 2014 concerning amendments to Law Number 23 of 2002 concerning Child Protection. Judicial legal considerations in imposing criminal sanctions on imprisonment against children are legal judicial considerations and social conditions of children and their environment.